TOETVA parathyroid autofluorescence detection: hANDY-i endoscopy attachment - Seo, Stefanie; Ali, Khalid Mohamed; Wolfe, Samantha A.; Nagururu, Nimesh V.; Ding, Andy S.; Desai, Dipan; Harbison, R. Alex; Kim, Yoseph; Ning, Bo; Cha, Richard Jaepyeong; Russell, Jonathon O. (Frontiers in Endocrinology, 2023)
Background Treatment options for thyroid pathologies have expanded to include scarless and remote access methods such as the transoral endoscopic thyroidectomy vestibular approach (TOETVA). Currently, no standardized methods exist for locating parathyroid glands (PGs) in patients undergoing TOETVA, which can lead to parathyroid injury and subsequent hypocalcemia. This early feasibility study describes and evaluates the hANDY-i endoscopic attachment for detecting PGs in transoral thyroidectomy. Methods We used a prototype parathyroid autofluorescence imager (hANDY-i) that was mounted to a 10-mm 0-degree endoscope. The device delivers a split screen view of Red-green-blue (RGB) and near-infrared autofluorescence (NIRAF) which allows for simultaneous anatomical localization and fluorescence visualization of PGs during endoscopic thyroid dissection. Results One cadaveric case and two patient cases were included in this study. The endoscopic hANDY-i imaging system successfully visualized PGs during all procedures. Conclusion The ability to leverage parathyroid autofluorescence during TOETVA may lead to improved PG localization and preservation. Further human studies are needed to assess its effect on postoperative hypocalcemia and hypoparathyroidism.